Antibiotic Strategies for Severe Community-Acquired Pneumonia - Bassetti, Matteo; Giacobbe, Daniele R.; Magnasco, Laura; Fantin, Alberto; Vena, Antonio; Castaldo, Nadia (Seminars in Respiratory and Critical Care Medicine, 2024)
Despite advancements in health systems and intensive care unit (ICU) care, along with the introduction of novel antibiotics and microbiologic techniques, mortality rates in severe community-acquired pneumonia (sCAP) patients have not shown significant improvement. Delayed admission to the ICU is a major risk factor for higher mortality. Apart from choosing the appropriate site of care, prompt and appropriate antibiotic therapy significantly affects the prognosis of sCAP. Treatment regimens involving ceftaroline or ceftobiprole are currently considered the best options for managing patients with sCAP. Additionally, several other molecules, such as delafloxacin, lefamulin, and omadacycline, hold promise as therapeutic strategies for sCAP. This review aims to provide a comprehensive summary of the key challenges in managing adults with severe CAP, focusing on essential aspects related to antibiotic treatment and investigating potential strategies to enhance clinical outcomes in sCAP patients.
Keywords: ceftobiprole; ceftaroline; sCAP; community-acquired pneumonia; ICU; new antibiotics